2019
DOI: 10.21203/rs.2.10906/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Improved Clinical Outcome Using Transarterial Chemoembolization Combined with Radiofrequency Ablation for Patients in Barcelona Clinic Liver Cancer Stage A or B Hepatocellular Carcinoma Regardless of Tumor Size: Results of a Single-center Retrospective Case Control Study

Abstract: Background To determine the safety and efficacy of transarterial chemoembolization (TACE) combined with radiofrequency ablation (hereafter, TACE-RFA) in treating Barcelona Clinic Liver Cancer (BCLC) Stage A or B (hereafter, BCLC A/B) hepatocellular carcinoma (HCC) patients, and to explore the range of tumor sizes suitable for combination therapy. Methods This retrospective study assessed the consecutive medical records of HCC patients with BCLC A/B who received TACE-RFA or TACE from September 2009 to September… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…With the development of the imaging-guided location, artificial hydrothorax, and perioperative management, aggressive therapies (including but not limited to RFA and liver resection) are no longer contraindications but alternative treatment options in advanced HCC. Recently, a growing number of studies have indicated the application of RFA in patients with intermediate-and advanced-stage HCC, including patients with tumor thrombus (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…With the development of the imaging-guided location, artificial hydrothorax, and perioperative management, aggressive therapies (including but not limited to RFA and liver resection) are no longer contraindications but alternative treatment options in advanced HCC. Recently, a growing number of studies have indicated the application of RFA in patients with intermediate-and advanced-stage HCC, including patients with tumor thrombus (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the extent of thermal ablation is generally limited, although this can be compensated for by repeated operations, but the possibility of omission exists [36]. Furthermore, after the arterial blood supply of tumor is destroyed by thermal coagulation, subsequent follow-up treatment, such as transcatheter arterial chemoembolization, is highly required [37,38]. We believe that these observations are the reasons tumors are more likely to recur after RFA treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A string of image-guided percutaneous ablations encompasses a great variety of techniques, including radiofrequency ablation (RFA), microwave ablation (MWA), ethanol injection, and cryoablation [62][63][64][65]. As RFA is the most frequently used ablation modality for HCC [66,67], the main topic addressed in this section is RFA.…”
Section: Local Ablationmentioning
confidence: 99%